2018
DOI: 10.1080/10826068.2018.1479864
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, antimicrobial, antioxidant, and anticoagulant activities of silver nanoparticles synthesized from Petiveria alliacea L. leaf extract

Abstract: Phytosynthesis of silver nanoparticles (AgNPs) using leaf extract of Petiveria alliacea (PA) was the focus of this research work. The PA-AgNPs were characterized by UV-Vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and selected area electron diffraction (SAED) study. Studies were made on the AgNPs for antibacterial, antifungal, anticoagulant, free-radical scavenging, and hydrogen peroxide scavenging activities. The crystalline PA-AgNPs were monodispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 50 publications
2
50
1
1
Order By: Relevance
“…The optical microscopic micrographs revealed the effective dispersion of disc‐like red blood cells due to reaction of blood clot with the biosynthesized Ag‐AuNPs. The results in this study are in line with some previous reports on the anticoagulant and thrombolytic potentials of Ag‐AuNPs, AgNPs, and AuNPs . Most recently, we documented a review on the applications of nanoparticles for the control and management of blood coagulation disorders …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The optical microscopic micrographs revealed the effective dispersion of disc‐like red blood cells due to reaction of blood clot with the biosynthesized Ag‐AuNPs. The results in this study are in line with some previous reports on the anticoagulant and thrombolytic potentials of Ag‐AuNPs, AgNPs, and AuNPs . Most recently, we documented a review on the applications of nanoparticles for the control and management of blood coagulation disorders …”
Section: Resultssupporting
confidence: 91%
“…These attributes are very important in the management of blood coagulation disorders using nano-based products. 87 Ag-AuNPs, 5,13 AgNPs, 14,17,52,74,88 and AuNPs. 5,7 Most recently, we documented a review on the applications of nanoparticles for the control and management of blood coagulation disorders.…”
Section: Anticoagulant and Thrombolytic Potentials Of Ag-aunpsmentioning
confidence: 99%
“…Biological methods involve simple bioreduction methods and need not separate capping processes and separate capping agents. AgNPs have been prepared using different plant extracts including Gymnema sylvestre [36], Centella asiatica [37], Melia dubia [38], Rhynchosia suaveolens [39], Shorea roxburghii [40], Morus alba [41], Priva cordifolia [42], Catharanthus roseus [43], Andrographis paniculata [44], Cordia dichotoma [45], Cassia angustifolia [46], Amaranthus cruentus [47], Cola nitida [48], Arnebia hispidissima [49], Petiveria alliacea [50], Persea Americana [51], Buchanania axillaris [52], and Jatropha curcas [53] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesized AgNPs using the extracts of cobweb, pod, seed and seed shell of C. nitida achieved 77.0-99.8 % scavenging of H2O2. Similarly, Petiveria alliacea leaf extract-mediated AgNPs(Lateef et al, 2018b) were shown to scavenge H2O2 and DPPH by 89.02 and 70.69 %, respectively Elegbede et al (2018a). also reported xylanase-mediated AgNPs to have scavenged DPPH and H2O2 by 37.48-79.42 and 20.50-96.50 % respectively.…”
mentioning
confidence: 90%